Where is echinoderm aquaculture heading in Latin America? Potential, challenges and opportunities. - Sonnenholzner-Varas, Jorge-I. (2021)
Introduction: Echinoderm aquaculture in Latin America is incipient, but it represents a new frontier for the highly nutritious marine food production, with native species of high commercial value offering a vast potential when compared to the weakened artisanal benthic fisheries. Methodology: We reviewed the literature on sea cucumbers, sea urchins, and starfish up to the year 2020. Results: By 2020, there were 17 native species with important advances in reproduction, larviculture, growth, treatment and identification of diseases, and nutrition, in Mexico, Belize, Panamá, Colombia, Ecuador, Peru, Brazil, Chile and Argentina. Conclusions: Echinoderm aquaculture in Latin America is advancing and would benefit from multitrophic systems to expand and diversify, reducing the pressure on depleted fisheries.